Ligand‐Promoted C(sp3)−H Olefination en Route to Multi‐functionalized Pyrazoles. Issue 21 (15th April 2016) - Yang, Weibo; Ye, Shengqing; Schmidt, Yvonne; Stamos, Dean; Yu, Jin‐Quan
Abstract: A Pd‐catalyzed/N‐heterocycle‐directed C(sp 3 )−H olefination has been developed. The monoprotected amino acid ligand (MPAA) is found to significantly promote Pd‐catalyzed C(sp 3 )−H olefination for the first time. Cu(OAc)2 instead of Ag + salts are used as the terminal oxidant. This reaction provides a useful method for the synthesis of alkylated pyrazoles. Abstract : The right moves : A pyrazole‐directed C(sp 3 )−H olefination has been developed (see scheme). The monoprotected amino acid ligands (MPAA) are found to significantly promote the reactivity in Pd‐catalyzed C(sp 3 )−H olefination. The applicability of using this reaction for late‐stage diversification of pyrazole‐based complex scaffold is demonstrated.